DEVELOPMENT OF PRIMARY CELL CULTURE FROM TAIL EPIDERMAL TISSUE OF KOI CARP (Cyprinus carpio koi) - Lila Gardenia; Isti Koesharyani (Indonesian Aquaculture Journal, 2014)
Primary cell culture from tail epidermal tissue of koi carp (Cyprinus carpio koi) was developed. Cells were grown in Leibovits-15 medium supplemented with 20% fetal bovine serum and antibiotics (Penicillin/Streptomycin and Kanamycin). Cell growth was observed in a range of incubation temperature (17oC±2oC, 22oC±2oC, 27oC±2oC, and 32oC±2oC) in order to determine the optimum temperature. The cells were able to grow at a range of temperature between 17oC to 32oC with optimal growth at 22oC. Primary cells infected with koi herpes virus produced typical cytopathic effects characterized by severe vacuolation and deformation of nuclei, which is consistent with those of previous reports. Artificial injection experiment by using supernatant koi herpes virus SKBM-1 isolate revealed that it could cause 90% mortality in infected fish within two weeks. PCR test with Sph I-5 specific primers carried out with DNA template from supernatant virus, pellet cell, and gills of infected fish showed positive results in all samples (molecular weight of DNA target 290 bp). The cells were found to be susceptible to koi herpes virus and can be used for virus propagation.